A comprehensive evaluation of basic health facilities according to local standards and demographic features of umarkot sub-region, Pakistan - Talpur, M.A.H. (Maxwell Science Publications, 2014)
The population of developing countries is increasing with its pace, which put a negative impact on the availability of services, especially accessible health facilities in destitute sub-regions. The shortage of basic health institutions created havoc in deprived sub-regions, which shattered the health structure of common men. There could be many reasons behind, but the most prominent could be the unavailability of health institutions, according to local standards and sub-regional demographic characteristics. Therefore, the goal of this research is to investigate the health and population features of the study area and to determine the existing and futuristic shortage of basic health institutions, according to local standards of the country. To comply with study objectives, the data were collected through field visits, interviews with the officials and with the help of available documents, i.e., district census report. The aims of the study were achieved and it was found that the health sector of the study area was not in its satisfactory condition. The findings of this study may provide a vision to the policy makers in a sense that they could pay their attention to the shaky condition of the health sector, especially in backward sub-regions of the country.Â© Maxwell Scientific Organization, 2014.